2019
DOI: 10.1186/s12916-019-1380-z
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease: a comprehensive current review

Abstract: Background Celiac disease remains a challenging condition because of a steady increase in knowledge tackling its pathophysiology, diagnosis, management, and possible therapeutic options. Main body A major milestone in the history of celiac disease was the identification of tissue transglutaminase as the autoantigen, thereby confirming the autoimmune nature of this disorder. A genetic background ( HLA-DQ2/DQ8 positivity and non-HLA genes) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
574
1
76

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(798 citation statements)
references
References 183 publications
9
574
1
76
Order By: Relevance
“…NRCD can be categorized as primary, where there is no response to a GFD, or secondary, where individuals initially respond to a GFD, but then develop symptoms despite ongoing adherence to a GFD [3]. Some expert gastroenterologists have suggested that the definition of NRCD causes confusion, primarily because the underlying cause of symptoms in these individuals may be related, or unrelated, to CD [6]. In contrast, we consider this definition appropriate, as it puts CD at the forefront of the clinical approach when considering the causes of persisting symptoms in these patients.…”
Section: Defining Non-responsive Coeliac Diseasementioning
confidence: 99%
“…NRCD can be categorized as primary, where there is no response to a GFD, or secondary, where individuals initially respond to a GFD, but then develop symptoms despite ongoing adherence to a GFD [3]. Some expert gastroenterologists have suggested that the definition of NRCD causes confusion, primarily because the underlying cause of symptoms in these individuals may be related, or unrelated, to CD [6]. In contrast, we consider this definition appropriate, as it puts CD at the forefront of the clinical approach when considering the causes of persisting symptoms in these patients.…”
Section: Defining Non-responsive Coeliac Diseasementioning
confidence: 99%
“…Celiac disease is part of the autoimmune inflammatory disease family targeting the small intestine. The disease is triggered by the ingestion of the prolamins contained in wheat, barley, rye, or oat, by genetically susceptible individuals [39]. The average incidence of CD is 1% in the Western world.…”
Section: Celiac Disease In a Nutshellmentioning
confidence: 99%
“…Research has supported the idea that the deregulated expression and function of TG contributes to pathological conditions such as cancer metastasis, tissue fibrosis, coeliac disease and neurodegenerative disorders . The coeliac disease is a gluten‐induced immune‐mediated disease characterised by a specific genetic genotype (HLA‐DQ2 and HLA‐DQ8 genes) and autoantibodies (anti‐tissue transglutaminase) . A key player is transglutaminase 2, which is able to modify gluten‐derived gliadin peptide .…”
Section: Introductionmentioning
confidence: 99%